PORTFOLIO ASSESSMENT IN PRIMARY SCHOOLS - M. Khairul Rizal; Rochmiyati Rochmiyati; Alben Ambarita; Een Yayah Hainilah (Jurnal Ilmiah Teunuleh, 2021)
The purpose of this study is to describe the portfolio assessment conducted by the teacher on students and to describe the results of the use of the portfolio assessment. This study uses a qualitative method. This research is to obtain descriptive data regarding the implementation of the portfolio assessment conducted by the teacher on students, and a description of the results obtained by the teacher and students in carrying out the portfolio assessment process. From the results of this study, it can be seen thatteachers should be prepared to make written and standardized assessment criteria when they have decided to use portfolio assessment so that the assessment is carried out in accordance with existing achievement indicators. However, from the data seen, teachers often assess student assignments outside of learning hours so that the involvement of students in the assessment process is still not illustrated.